2019
DOI: 10.1136/archdischild-2018-316664
|View full text |Cite
|
Sign up to set email alerts
|

Improving incidence trends of severe intraventricular haemorrhages in preterm infants <32 weeks gestation: a cohort study

Abstract: ObjectiveTo describe the trend and risk factors for severe intraventricular haemorrhage (IVH) among infants <32 weeks gestation.DesignPopulation-based cohort study.SettingAustralia and New Zealand.PatientsAll preterm infants <32 weeks gestation in the Australian and New Zealand Neonatal Network (ANZNN) from 1995 to 2012.InterventionsComparison of IVH incidence between 6-year epochs.Main outcome measuresOverall IVH and severe IVH incidence.ResultsA total of 60 068 infants were included, and overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 42 publications
3
38
5
2
Order By: Relevance
“…GMH-IVH infants had a significantly lower GA and Apgar score compared to controls. This is consistent with previous data investigating the predictive risk factors for GMH-IVH development (22,23). Although an inverse correlation between TOHRx and GA has been previously reported (12), in the present study the between-group difference was observed only before, and not after GMH-IVH development.…”
Section: Discussionsupporting
confidence: 93%
“…GMH-IVH infants had a significantly lower GA and Apgar score compared to controls. This is consistent with previous data investigating the predictive risk factors for GMH-IVH development (22,23). Although an inverse correlation between TOHRx and GA has been previously reported (12), in the present study the between-group difference was observed only before, and not after GMH-IVH development.…”
Section: Discussionsupporting
confidence: 93%
“…Overall and in all subgroups of weight and gestation for any IVH and high grade IVH, our rates of IVH are higher than those reported in HICs. The difference is smallest in the <1500g and <28 week gestation groups and largest in babies weighing >1500g or >37 weeks, suggesting in our setting it could be the higher weight and later gestation babies that could bene t most from modi cation of risk factors (13)(14)(15)(16)26) .…”
Section: Discussionmentioning
confidence: 71%
“…When assessed by GA, of those born at <28 weeks GA, 32-33.9% have IVH, 12.6-16% severe (13,15). More mature neonates born at <32 weeks have reported IVH prevalence of 21.4-23.1% (14,16). In HICs, high grade IVH leads to cerebral palsy in about 30% of cases, mainly but not only related to the site of parenchymal haemorrhagic infarction, in addition to other developmental and neurosensory impairments (15).…”
Section: Introductionmentioning
confidence: 99%
“…The respiratory management and treatment of infants born to mothers with COVID-19 is another consideration. Antenatal steroids decrease the risk of adverse preterm infant outcomes, [75][76][77] but may also pose a theoretical risk of worsening maternal viraemia. 78,79 Conversely, steroids reduce the cytokine storm, especially if maternal acute respiratory distress syndrome is evident.…”
Section: Discussionmentioning
confidence: 99%